MEASURING THE FUNDAMENTAL ATTRACTIVENESS OF PALM OIL BUSINESS AMIDST THE LEGITIMACY CRISIS: THE MODERATING ROLE OF OIL EXTRACTION RATE ON THE INFLUENCE OF INTEREST COVERAGE RATIO AND EBITDA MARGIN ON STOCK PRICES - Thezar Fiqih Hidayat Hasibuan (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
Industry coconut Central Indonesian palm oil at a crossroads paradoxical : in one side face crisis legitimacy scale national follow 4.09 million in order hectares garden palm oil illegal in area forest by Unit Task Forest Area Regulation , while on the other hand recording foreign exchange export highest throughout history amounting to US$ 35.87 billion by 2025. Research This aim test Is the capital market stable? appreciate the fundamentals of resilience financial issuer plantation palm oil in the middle pressure legitimacy said , with positioning the interest coverage ratio (ICR) and EBITDA margin as predictor price share as well as oil extraction rate (OER) as variables moderation . Balanced panel data collected from ten issuer plantation palm oil on the Indonesia Stock Exchange during period 2023 to first quarter 2026 (40 observations ) and analyzed using moderated regression analysis based on panel data regression with error standard clustered . Estimation results show that ICR and EBITDA margin have an effect positive significant to price OER shares are proven strengthen the influence of EBITDA margin on price shares (β = 88.535; p = 0.011) and behave as moderator pure , but No moderate ICR influence . Simple slopes analysis confirms that sensitivity price share to profitability increase in a way monoton along increase yield . Findings This indicates that investors do differentiation fundamentally based instead of punish industry in a way collectively , so that Power lure business palm oil for perpetrator business rooted in profitability whose credibility amplified by excellence operational agronomist .